Identifying Risk Factors Associated with the Development of Diabetic Retinopathy in Local Population - Tariq, Erum; Waheed, Palvasha; Rashid, Amir; Majeed, Asifa (Pakistan Armed Forces Medical Journal, 2022)
Objective: To identify the risk factors for developing diabetic retinopathy.Study Design: Cross-sectional study.Place and Duration of Study: Department of Biochemistry and Molecular Biology, Army Medical College, Rawalpindi, PakEmirates Military Hospital (PEMH), Rawalpindi and Armed Forces Institute of Ophthalmology (AFIO), Rawalpindi Pakistan,from Jun 2021 to May 2022.Methodology: A total of one hundred and fifty participants aged 25-70 years were included in the study. All participants weredivided into three equal groups. Group-I was of age and gender-matched healthy individuals (n=50), Group-II was of peoplewith diabetes without retinopathy (n=50), and Group-III was of diabetic patients having retinopathy (n=50). All the data of theparticipants were recorded on an especially designed proforma, and 5ml of venous blood was also drawn from the subjects tomeasure serum lipid levels.Results: Male gender was more common with 33(66%), 30(60%) and 33(66%) in Group-I, Group-II, and Group-III respectively.Most of the retinopathy cases had sedentary lifestyle 33(66%), poor dietary habits 34(68%), cardiovascular disease 38(76%),diabetic foot ulcers 44(88%) and increased levels of TAGS (p-value 0.001). Nephropathy and smoking showed no significantlink with dr.Conclusion: It can be concluded that a sedentary lifestyle, poor dietary habits, cardiovascular disease, diabetic foot andincreased TAGS may be risk factors for the development of diabetic retinopathy. These findings can help in the earlyidentification and better prognosis of the disease in high-risk individuals.